ACTAR Arquitectura : Llull-Taulat, manzana 3, bloque PB+3 (2002)
Proyecto de renovación urbana en Barcelona con motivo del Fórum.
Keywords: ACTAR ARQUITECTURA; BARCELONA; ESPAÑA; PROYECTOS; VIVIENDAS MULTIFAMILIARES; VIVIENDAS COLECTIVAS; FORUM